2004 International Pipeline Conference, Volumes 1, 2, and 3 2004
DOI: 10.1115/ipc2004-0364
|View full text |Cite
|
Sign up to set email alerts
|

Buckling Resistance of Large Diameter Spiral Welded Linepipe

Abstract: This paper contains the results of an experimental and analytical research program to determine the compressive buckling resistance of large-diameter, spiral-welded linepipe. Buckling resistance is important for pipe intended for service in Arctic, oil and gas pipeline systems, where pipes may be subjected to high bending strains caused by various ground movement events. The experimental work consisted of four full-scale tests of 30-inch (762 mm) diameter pipe subjected to various combinations of internal pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…[2][3][4]. Studies have shown that, in comparison to UOE pipes, spiral pipes can have equivalent or better properties regarding to bending [5], plastic collapse [6], bursting [7], ductile tearing [8] or buckling resistance [4,9]. Also, it has been shown that the fatigue resistance and fracture arrest properties are at least equivalent to those of UOE pipes [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4]. Studies have shown that, in comparison to UOE pipes, spiral pipes can have equivalent or better properties regarding to bending [5], plastic collapse [6], bursting [7], ductile tearing [8] or buckling resistance [4,9]. Also, it has been shown that the fatigue resistance and fracture arrest properties are at least equivalent to those of UOE pipes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The use of spiral welded pipes could potentially lead to a project cost reduction of 5-15% compared to UOE pipes, which makes them attractive for industrial use. [4,9]. Also, it has been shown that the fatigue resistance and fracture arrest properties are at least equivalent to those of UOE pipes [10,11].…”
mentioning
confidence: 99%
“…The study concludes that the spiral weld seam may not be detrimental to tube performance and that spiral-welded line pipe performs as good as longitudinal welded linepipe in terms of local buckling behavior. Further experimental testing on spiral-welded tubes was performed by Salzgitter Mannesmann, reported by Zimmermann et al [27]. In that research, four-point bending tests were performed on four spiral-welded tubes.…”
Section: Figurementioning
confidence: 99%
“…In order to evaluate the validity of the numerical simulation, the results were calibrated with previous experimental results (Zimmerman et al 2004). Four specimens were used to study the local buckling behavior in experiments, including two material grades X70 and X80.…”
Section: Model Calibrationmentioning
confidence: 99%
“…In this paper, a practical three-dimensional model was established using the nonlinear finite element method (FEM) and calibrated with previous experimental results (Zimmerman et al 2004). After that, deformation behavior and different failure modes of unpressurized and pressurized pipes were studied under bending conditions.…”
Section: Introductionmentioning
confidence: 99%